2021
DOI: 10.1186/s12911-021-01670-z
|View full text |Cite
|
Sign up to set email alerts
|

Implementation challenges and perception of care providers on Electronic Medical Records at St. Paul’s and Ayder Hospitals, Ethiopia

Abstract: Background In resources constrained settings, effectively implemented Electronic Medical Record systems have numerous benefits over paper-based record keeping. This system was implemented in the 2009 Gregorian Calendar in the two Ethiopian territory hospitals, Ayder and St. Paul’s. The pilot implementation and similar re-deployment efforts done in 2014 and 2017 Gregorian Calendar failed at St. Paul's. This study aimed to assess the current status, identify challenges, success factors and percep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 25 publications
2
21
1
Order By: Relevance
“…In addition, they also recorded injuries related to posture and duration of time required to complete electronic forms on bedside touch screens, and negative comments contradicted by observational data [21]. Similarly, the statement by Leenan et al that there is still dissatisfaction in the use of electronic devices such as alarms due to system malfunctions, alarm frequency and dissonance with nurse measurements [22], and also found the low acceptance in the implementation of information systems, lack of training and support as inhibiting factors [23], [24]. However, positive perceptions are found in the use of management information systems and alarms, where electronic systems are very useful and easy to be used by nurses since they are efficient in storing patient data [22], [23].…”
Section: Effects Of Using Digital Technology In Achieving Nurse Job S...mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, they also recorded injuries related to posture and duration of time required to complete electronic forms on bedside touch screens, and negative comments contradicted by observational data [21]. Similarly, the statement by Leenan et al that there is still dissatisfaction in the use of electronic devices such as alarms due to system malfunctions, alarm frequency and dissonance with nurse measurements [22], and also found the low acceptance in the implementation of information systems, lack of training and support as inhibiting factors [23], [24]. However, positive perceptions are found in the use of management information systems and alarms, where electronic systems are very useful and easy to be used by nurses since they are efficient in storing patient data [22], [23].…”
Section: Effects Of Using Digital Technology In Achieving Nurse Job S...mentioning
confidence: 99%
“…This study discovered that there were 10 articles on ICT in nursing services such as the use of EHR [23], [24], [29]. It also includes HIT, ICT or implementing E-Health, and PAEHR [27], [19], [26], [20], [31], implementation of a novel electronic bedside nursing chart [21], while digital technology is also related to technology [30].…”
Section: Various Types Of Technology Applied By Nursesmentioning
confidence: 99%
“…In the USA, the Meaningful Use (MU) program was established to facilitate nationwide adoption of EMRs, and resulted in a steep increase in EMR implementation, leading to > 90% of hospitals using a government-certified EMR [ 3 ]. Globally, EMR implementation is also increasing, albeit to varying degrees across different countries [ 5 , 6 ]. The widespread of EMR implementation has exposed several challenges [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Various studies from developed countries have revealed that EHR, has many benefits, such as having the ability to reduce waiting times, keeping safe records of past medical events, as well as easy accessibility of patient data during referrals [ 5 , 14 , 15 , 24 ]. However, it is the extent of the quality of the electronic health records that determines the fast access to patient information thereby facilitating health care provider communication, health care continuity and improved quality of care [ 4 , 11 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the benefits stated by many authors, some facilities are not enjoying these benefits because of some barriers or challenges as enumerated by some studies regarding the use of EHR [ 5 , 9 , 13 , 23 ]. These include inadequate computer skills, limited or non-available tools, limited funding, lack of technical basis, security and privacy issues, lack of technical expertise and, changes in workflow.…”
Section: Introductionmentioning
confidence: 99%